Historia Silense / edición, crítica e introducción por Dom Justo Pérez de Urbel, O.S.B., y Atilano González Ruiz Zorrilla - Pérez de Urbel, JustoGonzález Ruiz-Zorrilla, Atilano (Textos; 30)
Bibliografía: p. 213-215. Índices